Phase III Trial of Avelumab Maintenance After First-Line Induction Chemotherapy Versus Continuation of Chemotherapy in Patients With Gastric Cancers: Results From JAVELIN Gastric 100. Issue 9 (20th March 2021) - Moehler, Markus; Dvorkin, Mikhail; Boku, Narikazu; Özgüroğlu, Mustafa; Ryu, Min-Hee; Muntean, Alina S.; Lonardi, Sara; Nechaeva, Marina; Bragagnoli, Arinilda C.; Coşkun, Hasan S.; Cubillo Gracian, Antonio; Takano, Toshimi; et al.
Abstract : PURPOSE: The role of maintenance therapy for gastric (GC) or gastroesophageal junction cancer (GEJC) is unclear. We investigated avelumab (anti–programmed death ligand-1 [PD-L1]) maintenance after first-line induction chemotherapy for GC/GEJC. PATIENTS AND METHODS: JAVELIN Gastric 100 was a global, open-label, phase III trial. Eligible patients had untreated, unresectable, human epidermal growth factor receptor 2–negative, locally advanced or metastatic GC or GEJC. Patients without progressive disease after 12 weeks of first-line chemotherapy with oxaliplatin plus a fluoropyrimidine were randomly assigned 1:1 to avelumab 10 mg/kg every 2 weeks or continued chemotherapy, stratified by region (Asia v non-Asia). The primary end point was overall survival (OS) after induction chemotherapy in all randomly assigned patients or the PD-L1–positive randomly assigned population (≥ 1% of tumor cells; 73-10 assay). RESULTS: A total of 805 patients received induction; 499 were randomly assigned to avelumab (n = 249) or continued chemotherapy (n = 250). Median OS was 10.4 months (95% CI, 9.1 to 12.0 months) versus 10.9 months (95% CI, 9.6 to 12.4 months) and 24-month OS rate was 22.1% versus 15.5% with avelumab versus chemotherapy, respectively (hazard ratio [HR], 0.91; 95% CI, 0.74 to 1.11; P = .1779). In the PD-L1–positive population (n = 54), the HR for OS was 1.13 (95% CI, 0.57 to 2.23; P = .6352). In an exploratory analysis of the PD-L1–positive population, defined as combined positive score ≥ 1 (22C3 assay; n = 137), median OS was 14.9 months (95% CI, 8.7 to 17.3 months) with avelumab versus 11.6 months (95% CI, 8.4 to 12.6 months) with chemotherapy (unstratified HR, 0.72; 95% CI, 0.49 to 1.05). With avelumab and chemotherapy, treatment-related adverse events (TRAEs) occurred in 149 (61.3%) and 184 (77.3%) patients, including grade ≥ 3 TRAEs in 31 (12.8%) and 78 (32.8%) patients, respectively. CONCLUSION: JAVELIN Gastric 100 did not demonstrate superior OS with avelumab maintenance versus continued chemotherapy in patients with advanced GC or GEJC overall or in a prespecified PD-L1–positive population.